Surgical lymph node assessment in mucinous ovarian carcinoma staging: a systematic review and meta‐analysis. (22nd July 2016) - Hoogendam, JP; Vlek, CA; Witteveen, PO; Verheijen, RHM; Zweemer, RP
Abstract : Background: The proportion of women with mucinous ovarian carcinoma in whom nodal metastases are identified during staging remains unclear. Objectives: To review the literature on surgical lymph node assessment during staging of women diagnosed with mucinous ovarian carcinoma. Search strategy: A systematic search using synonyms of 'mucinous ovarian carcinoma' and 'lymph node assessment' was conducted in PubMed, Scopus, Embase and the Cochrane Library. Selection criteria: When they covered ten or more mucinous ovarian carcinoma cases, staging surgery and minimally one of the following outcomes: prevalence of metastases, stage shift or survival data. Data collection and analysis: Studies were quality evaluated with the Cochrane risk‐of‐bias assessment tool for non‐randomised studies of interventions. Outcomes were pooled using an inverse variance weighted random effects model. Main results: Sixteen studies were included. In 278 women with mucinous ovarian cancer suspected to be stage I–II, a pooled proportion of 0.8% (95% CI <0.1–2.9%) had lymph node metastases and were upstaged. In those suspected of stage I ( n = 184), this proportion was 0.7% (95% CI <0.1–3.8%). No difference ( P = 0.287) was found in metastases between sampling at 0.0% (95% CI 0.0–3.3%) and complete pelvic and/or para‐aortic lymph node dissection at 1.2% (95% CI <0.1–4.2%). One study directly compared the survival of patients staged with and without lymph node dissection and reported no significant difference. Conclusions: Surgical lymph node assessment in women suspected of stage I–II mucinous ovarian carcinoma rarely identifies nodal metastases and consequently has no significant impact on staging. Tweetable abstract: Surgical lymph node assessment in women with stage I–II mucinous ovarian cancer rarely has staging consequences. Tweetable abstract: Surgical lymph node assessment in women with stage I–II mucinous ovarian cancer rarely has staging consequences.